Relationship Between Health Perception and Cervical Cancer Awareness: Two Different Data Collection Methods - Fatma Genç; Çağla Yiğitbaş (Galenos Publishing House, 2024)
Objective: Cervical Cancer (CC) is one of the most common cancers in women. CC screenings are performed free of charge at all stages of cancer early diagnosis and screening centers in women aged 30-65 years. The incidence of women in this age range to benefit from screenings is high. It is considered that this condition may cause a loss in terms of early diagnosis. This study aims to determine the relationship between health perception and CC awareness in terms of socio-demographic characteristics of women (primarily age) and two different data collection methods. Method: The research is in descriptive-sectional design. The population consisted of women aged 20-65 years. Four hundred seventy-eight people were included in the sample. The data were collected by personal information form, Health Perception Scale (HPS) and Attitude Scale Toward the Early Detection of Cervical Cancer (ASTEDCC). Results: The mean age was 34.27±10.32, the mean HPS was 40.86±8.24, and the mean ASTEDCC was 94.38±12.09. It was found that being 36 years and older, having children, having heard of the test, made a difference in getting a pap smear test. The mean rank of ASTEDCC was higher in patients with face-to-face interview methods. A positive and moderate relationship was found between HPS and ASTEDCC. Conclusion: Age and the way the data were collected from the participants are effective in CC awareness and there is a relationship between health perception and CC awareness.